Cardiovascular mortality in Dutch men during 1996 European football championship: longitudinal population study. Issue 7276 (23rd December 2000) - Witte, Daniel R; Bots, Michiel L; Hoes, Arno W; Grobbee, Diederick E
Abstract: Objective: To investigate whether an important football match increases stress to such an extent that it triggers acute myocardial infarction and stroke. Design: Longitudinal study of mortality around 22 June 1996 (the day the Dutch football team was eliminated from the European football championship). Mortality on 22 June was compared with the five days before and after the match and in the same period in 1995 and 1997. Setting: Netherlands. Subjects: Dutch population aged 45 years or over in June 1996. Main outcome measures: All cause mortality and mortality due to coronary heart disease and stroke. Results: Mortality from coronary heart disease and stroke was increased in men on the day of the match (relative risk 1.51, 95% confidence interval 1.08 to 2.09). No clear rise in mortality was observed for women (1.11, 0.80 to 1.56). Among men, about 14 excess cardiovascular deaths occurred on the day of the match. Conclusion: Important sporting events may provoke a sufficient level of stress to trigger symptomatic cardiovascular disease. The difference between men and women requires further investigation.